Linux and the Unix philosophy - Gancarz, Mike. (Amsterdam ; Boston : Digital Press, 2003)
Unlike so many books that focus on how to use Linux, Linux and the Unix Philosophy explores the "way of thinking that is Linux" and why Linux is a superior implementation of this highly capable operating system. This book is a revision and expansion of a computer science classic. Every chapter has been thoroughly updated with Linux coverage. Linux and the Unix Philosophy falls squarely between the "softer" texts on iterative software design and project management and the "how-to" technical texts. Thus far, no one has come out with a book that addresses this topic, either in the Unix space or the Linux space. Linux and the Unix Philosophy covers the same ground as the first edition, while it also presents bold new ideas about Linux and Open Source. Concise list of philosophy tenets makes it a handy quick reference Anecdotal examples personalize the book for the reader Conversational style makes it easy and joyful to read.
The Unix philosophy : a cast of thousands -- One small step for humankind -- Rapid prototyping for fun and profit -- The portability priority -- Now that's leverage! -- The perils of interactive programs -- More Unix philosophy : ten lesser tenets -- Making Unix do one thing well -- Unix and other operating system philosophies -- Through the glass darkly : Linux vs. Windows -- A cathedral? how bizarre! -- Brave new (Unix) world.
Includes bibliographical references and index.
Keywords: Linux; UNIX (Computer file); Operating systems (Computers).; Electronic books